PKM Kegiatan Bakti Sosial “Delapan” (Delta Peduli Lingkungan) sebagai Wujud Kepedulian dan Cinta Lingkungan Bersama Masyarakat Desa Lerang, Kecamatan Lanrisang, Kabupaten Pinrang - Arwadi, Fajar; Sidjara, Sahlan; Armasari, Fanny; Djam'an, Nurwati; Rahman, Muhammad Fatur; Safitri N.N, Novi; Mutmainnah MR, Luthfiah; Sutamrin; Zaki, Ahmad (Jurnal Hasil-Hasil Pengabdian dan Pemberdayaan Masyarakat, 2023)
Real Work Lecture (KKN) is one form of community service activities by universities carried out by students under the guidance of lecturers and local government leaders. Through KKN, students can apply the knowledge they have acquired in college into real life. KKN-T students who have the post in Lerang Village made a work program in the form of “Eight” Social Service activities (Delta Cares for the Environment). Social service is an activity carried out by individuals or groups as a form of concern for the surrounding environment. Social service is carried out by cleaning the environment. The targets of social service activities are mosques, village offices, fields and the surrounding environment. In general, the “eight” social service activities (Delta Cares for the Environment) went well and smoothly. and get full support from the community and with this social service activity, it is hoped that the community will have the motivation to keep the environment clean.